2011
DOI: 10.1097/bot.0b013e3181f982e5
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Comparison of Tibial Nail Stability in a Proximal Third Fracture: Do Screw Quantity and Locked, Interlocking Screws Make a Difference?

Abstract: In this study, proximal segment stability was improved with a greater quantity of screws and with locked interlocking screws.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Several earlier studies involving the standard interlocking nail demonstrated construct slack due to less rigid interaction between the locking device and the nail hole (15,17,19,36). The BIN constructs with eight modified locking bolts had significantly higher stiffness, yield load and ultimate failure load than the constructs with eight standard bolts, which could be due to the snug fit of the modified locking bolts within the threaded holes of BIN, thereby reducing the slack in the fixation (21).…”
Section: Axial Compressionmentioning
confidence: 89%
See 4 more Smart Citations
“…Several earlier studies involving the standard interlocking nail demonstrated construct slack due to less rigid interaction between the locking device and the nail hole (15,17,19,36). The BIN constructs with eight modified locking bolts had significantly higher stiffness, yield load and ultimate failure load than the constructs with eight standard bolts, which could be due to the snug fit of the modified locking bolts within the threaded holes of BIN, thereby reducing the slack in the fixation (21).…”
Section: Axial Compressionmentioning
confidence: 89%
“…Higher values (approximately 1.5 times) of bending moment, stiffness, yield load and ultimate failure load for constructs with eight standard locking bolts than for constructs with four bolts is in agreement with the findings of previous studies with external skeletal fixation, where three-point fixation per bone segment was found to be more stable and stronger than two-point fixation (35). Similarly, constructs with modified locking bolts were also found significantly stronger than with standard bolts under bending, probably due to more rigid fixation with reduced intrinsic slack in the fixation (21). Earlier studies using an angle-stable locking nail have shown elimination of slack in both medio-lateral and cranio-caudal bending directions, in turn improving the construct stability in a canine tibial model (18,19).…”
Section: Three-point Bendingmentioning
confidence: 91%
See 3 more Smart Citations